ASAS-EULAR recommendations for the management of axial spondyloarthritis: 2022 update. Issue 1 (21st October 2022) - Ramiro, Sofia; Nikiphorou, Elena; Sepriano, Alexandre; Ortolan, Augusta; Webers, Casper; Baraliakos, Xenofon; Landewé, Robert B M; Van den Bosch, Filip E; Boteva, Boryana; Bremander, Ann; Carron, Philippe; Ciurea, Adrian; et al.
Abstract : Objectives: To update the Assessment of SpondyloArthritis international Society (ASAS)-EULAR recommendations for the management of axial spondyloarthritis (axSpA). Methods: Following the EULAR Standardised Operating Procedures, two systematic literature reviews were conducted on non-pharmacological and pharmacological treatment of axSpA. In a task force meeting, the evidence was presented, discussed, and overarching principles and recommendations were updated, followed by voting. Results: Five overarching principles and 15 recommendations with a focus on personalised medicine were agreed: eight remained unchanged from the previous recommendations; three with minor edits on nomenclature; two with relevant updates (#9, 12); two newly formulated (#10, 11). The first five recommendations focus on treatment target and monitoring, non-pharmacological management and non-steroidal anti-inflammatory drugs (NSAIDs) as first-choice pharmacological treatment. Recommendations 6–8 deal with analgesics and discourage long-term glucocorticoids and conventional synthetic disease-modifying antirheumatic drugs (DMARDs) for pure axial involvement. Recommendation 9 describes the indication of biological DMARDs (bDMARDs, that is, tumour necrosis factor inhibitors (TNFi), interleukin-17 inhibitors (IL-17i)) and targeted synthetic DMARDs (tsDMARDs, ie, Janus kinase inhibitors) for patients who have Ankylosing Spondylitis Disease Activity Score ≥2.1 and failed ≥2 NSAIDs and also have either elevated C reactive protein, MRI inflammation of sacroiliac joints or radiographic sacroiliitis. Current practice is to start a TNFi or IL-17i. Recommendation 10 addresses extramusculoskeletal manifestations with TNF monoclonal antibodies preferred for recurrent uveitis or inflammatory bowel disease, and IL-17i for significant psoriasis. Treatment failure should prompt re-evaluation of the diagnosis and consideration of the presence of comorbidities (#11). If active axSpA is confirmed, switching to another b/tsDMARD is recommended (#12). Tapering, rather than immediate discontinuation of a bDMARD, can be considered in patients in sustained remission (#13). The last recommendations (#14, 15) deal with surgery and spinal fractures. Conclusions: The 2022 ASAS-EULAR recommendations provide up-to-date guidance on the management of patients with axSpA.